TANTANGAN PERGURUAN TINGGI DI ERA REVOLUSI INDUSTRI 4.0 - Aryati, Seri (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The Industrial Revolution 4.0 received attention from Higher Education Institutions throughout the world. it is important to invite all Indonesians to carry out self-evaluations, why various problems such as: poverty; the gap between having and not; deforestation; land destruction; and the revolutionary storm of the fourth era of industry (Industry 4.0) will create unemployment; potential to expand economic inequality, etc. Furthermore, the question is how to make sustainable development after the 4th industrial revolution in Indonesia. The method in writing this paper uses qualitative descriptive. The purpose of this paper is to provide an overview of the conditions currently being faced by the Indonesian state due to the development of the industrial revolution 4.0 and provide an appropriate view for Indonesia to adopt innovations and applications for sustainable engineering and technology. Providing solutions for people to have a better life in Indonesia. Especially for universities in Indonesia, to be able to make good use of the industrial revolution 4.0. The government through cross-ministerial and agency policies issued various policies. One of the government's policies is the revitalization of Indonesian vocational education. Government support must include, 1) learning systems, 2) education units, 3) students, and 4) educators and education staff are also needed. Strengthening the four elements in the education system requires a new movement to respond to the industrial era 4.0.